Use of and Adherence to Antiretroviral Therapy in a Large U.S. Sample of HIV-infected Adults in Care, 2007-2008 - Beer, Linda (Bentham Open, 2012)
BACKGROUND: Antiretroviral therapy (ART) is the cornerstone of HIV clinical care and is increasingly recognized as a key component of HIV prevention. However, the benefits of ART can be realized only if HIV-infected persons maintain high levels of adherence. METHODS: We present interview data (collected from June 2007 through September 2008) from a national HIV surveillance system in the United States—the Medical Monitoring Project (MMP)—to describe persons taking ART. We used multivariate logistic regression to assess behavioral, sociodemographic, and medication regimen factors associated with three measures that capture different dimensions of nonadherence to ART: dose, schedule, and instruction. RESULTS: The use of ART among HIV-infected adults in care was high (85%), but adherence to ART was suboptimal and varied across the three measures of nonadherence. Of MMP participants currently taking ART, the following reported nonadherence during the past 48 hours: 13% to dose, 27% to schedule, and 30% to instruction. The determinants of the three measures also varied, although younger age and binge drinking were associated with all aspects of nonadherence. CONCLUSION: Our results support the measurement of multiple dimensions of medication-taking behavior in order to avoid overestimating adherence to ART.